(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2020)
The Spanish Civil War is an event that became the subject of many avant-garde works. The lives of poets in Spain were affected by the aforementioned event, most of the Spanish poets continued their life in exile. However, Latin American poets were also affected. Trying to answer the question: What is the reason for this?, we will comment on the influences on Latin American poets to elaborate on this theme. Then, the question of the close relationship between language and identity opens up because language is supposed to be the strongest and most important link between Latin American poets and their "European homeland" - Spain. In the cases of three poets, from Spain, Chile, and Argentina, we will analyze the similarities and differences between their visions of this war. In the paper, we will focus on the poem "Galope" by Alberti, "Explico algunas cosas" by Neruda, and Girondo’s story called "Interlunio". The reiteration of this theme in avant-garde works demands that we realize its importance and the comparative analysis offers a distinction between the universal and local aspects of its elaboration. That is at the same time the objective of our work - to emphasize the importance of the theme of the war that happened in Spain and to analyze its elaboration by three carefully selected poets. Keywords: The Spanish Civil War, Rafael Alberti, Pablo Neruda, Oliverio Girondo, poem.